2014
DOI: 10.1177/1468798414533562
|View full text |Cite
|
Sign up to set email alerts
|

Orchestrating literacies: Print literacy learning opportunities within multimodal intergenerational ensembles

Abstract: This exploratory case study considered the opportunities for print literacy learning within multimodal ensembles that featured art, singing and digital media within the context of an intergenerational programme that brought together 13 kindergarten children (4 and 5 years) with seven elder companions. Study questions concerned how reading and writing were practised within multimodal ensembles and what learning opportunities were afforded to the children while the participants worked through a chain of multimod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…When research has had literacy as a focus (eg Flewitt et al ., ) it has often revealed that teachers are eager use tablet technologies (iPads) as part of their early literacy programs. Further, when children use iPads, there is evidence that quality learning experiences that incorporate collaborations with others, communicating ideas and findings, as well as opportunities for independent learning (eg McKee & Heydon, ; Rowe & Miller, ).…”
Section: New Learning and Tablets In The Early Yearsmentioning
confidence: 99%
“…When research has had literacy as a focus (eg Flewitt et al ., ) it has often revealed that teachers are eager use tablet technologies (iPads) as part of their early literacy programs. Further, when children use iPads, there is evidence that quality learning experiences that incorporate collaborations with others, communicating ideas and findings, as well as opportunities for independent learning (eg McKee & Heydon, ; Rowe & Miller, ).…”
Section: New Learning and Tablets In The Early Yearsmentioning
confidence: 99%
“…Through interactions with their teachers and peers and through reading and writing a wide range of texts, students come to know what they can do with written language and visual images, and they construct understandings about written language. (p. 238) This idea of literacy as a social practice was also a central finding of the study by McKee and Heydon (2014). The intergenerational social activities within the literacy events of their study "allowed participants to share what was of import to them, and the participants drew on the modes and media that could help them accomplish the purpose of their communication" (McKee & Heydon, 2014, p. 25).…”
Section: Revue Des Sciences De L'éducation De Mcgill • Vol 52 N O 2 mentioning
confidence: 96%
“…McKee and Heydon (2014) orchestrated authentic writing tasks in their Intergenerational Digital Literacies Project. Elders from a local rest home were paired with kindergarten children to work on multimodal projects that included the use of art, singing, and digital technologies.…”
Section: Social Practices Discoursementioning
confidence: 99%
“…In this paper, we offer children's picturebook recommendations for educators to use with young children in learning spaces. The focus for this paper arises from our discussion in "Learning Together: Our Reflections on Connecting People and Practices in Intergenerational Meaning-Making Experiences" (McKee & Scheffel, this issue) where we reflect on our experiences as researchers / research assistants in intergenerational settings (McKee & Heydon, 2015;Scheffel, 2015). We ground our reflections in sociocultural perspectives that recognize meaning making as literacy that is dynamic, context specific, and supported through (1) relationships (Barton & Hamilton, 2000) and (2) the combination of different modes (written, visual, etc.…”
mentioning
confidence: 99%